Faith-based Messaging and Materials for Colorectal Cancer Screening in the United States: Application of Boot Camp Translation within the African Methodist Episcopal Church - Thompson, Jamie (Journal of religion and health, 2025)
The Black Church has long been an institution of refuge, mobilization, and healing in Black or African American communities. While health promotion interventions have been implemented in the Black Church, little is known about ways to incorporate faith into colorectal cancer (CRC) screening messages. Using modified boot camp translation, a community-based approach, we met with 27 members of the African Methodist Episcopal Church in Atlanta, Georgia, for in-person and virtual sessions to co-create faith-based CRC screening messages and identify channels for sharing information within the church community. Examples of messages developed included "Faith over fear" and "Honor God by taking care of your body." Identified dissemination channels included Sunday service, community events, and social media. Churches serve as key partners in delivering health information, as they are among the most trusted institutions within the Black or African American community.